Sikap Ilmiah dan Kreativitas Produk pada Isu Lingkungan melalui Pembelajaran Berbasiskan Proyek - YUSTINA, YUSTINA; SUWONDO, SUWONDO (Bioedukasi: Jurnal Pendidikan Biologi, 2015)
The purpose of this research was to got the information about student’s scientific attitude and creativity of product and correlation both of it in enviromental issues through project based learning. This research was conducted from January to June 2015. Sample in this research are 34 students of 2014 grade in FKIP Biologi UR used parameters are (1) scientific attitude with 4 indicators (curiosity, cooperative, carefulness and discipline); (2) creativity of product. Observation instrument managed by reseacher and the realibility values based Alfa Cronbach is 0.70-0.87. The creativity was scored through product (report) by using portofolio instrument, with descriptors are : Initiative (collecting information), inovation (environmental issues that are happening), variation of idea (way of display data), and suitable idea and their solution. The data analyzed is using SPSS. Descriptive statistic are percent, mean, standard deviation and inference statistic (Multiple regretion). Mean values shows us that student’s scientific attitude is 79,99 (good), and the creativity of product is 80,10 (good). Positive correlation among curiosity, cooperation, carefulness and discipline give contribution as 68% to determine the creativity of product. Separately, each aspect of student’s scientific attitude give contribution for creativity of product are : curiosity (60%), carefulness (57%), discipline (48%) and cooperative (47%). The conclusion is student’s scientific attitude and creativity of product is in good category, It mean was there are correlation between student’s scientific attitude and the creativity of product in environmental issues through project based learning in FKIP Biologi UR.